2022
DOI: 10.3390/molecules27082450
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of Sesquiterpene Chemistry Dictates Its Pleiotropic Biologic Effects on Inflammation

Abstract: Sesquiterpenes (SQs) are volatile compounds made by plants, insects, and marine organisms. SQ have a large range of biological properties and are potent inhibitors and modulators of inflammation, targeting specific components of the nuclear factor-kappaB (NF-κB) signaling pathway and nitric oxide (NO) generation. Because SQs can be isolated from over 1600 genera and 2500 species grown worldwide, they are an attractive source of phytochemical therapeutics. The chemical structure and biosynthesis of SQs is compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 171 publications
0
3
0
Order By: Relevance
“…Reduced levels of sesquiterpenes in drought-treated plants might have been due to the shift in terpene composition as our study period exceeded a month. Our results suggested that sesquiterpenes may probably be replaced by monoterpenes when drought is prolonged, because drought can impede the cyclization of sesquiterpene precursors ( Kopaczyk et al., 2020 ; Arizmendi et al., 2022 ). The increase in ABA content and the subsequent stomatal closure is also considered an important signaling event under drought stress across several species ( Bharath et al., 2021 ; Rehman et al., 2021 ).…”
Section: Discussionmentioning
confidence: 76%
“…Reduced levels of sesquiterpenes in drought-treated plants might have been due to the shift in terpene composition as our study period exceeded a month. Our results suggested that sesquiterpenes may probably be replaced by monoterpenes when drought is prolonged, because drought can impede the cyclization of sesquiterpene precursors ( Kopaczyk et al., 2020 ; Arizmendi et al., 2022 ). The increase in ABA content and the subsequent stomatal closure is also considered an important signaling event under drought stress across several species ( Bharath et al., 2021 ; Rehman et al., 2021 ).…”
Section: Discussionmentioning
confidence: 76%
“…Sesquiterpenes are the class of SM consisting of three isoprene units (C15) and are found in linear, cyclic, bicyclic, and tricyclic forms. Since sesquiterpenes have a high allergenic potential on the skin, their use in TP is limited [ 243 , 244 , 245 ].…”
Section: Natural Products From Plants Used In Medical Devicesmentioning
confidence: 99%
“…-Sesquiterpenes are the class of SM consisting of three isoprene units (C15) and are found in linear, cyclic, bicyclic, and tricyclic forms. Since sesquiterpenes have a high allergenic potential on the skin, their use in TP is limited [243][244][245]. -Diterpenoids belong to a versatile class of chemical constituents found in different natural sources having four isoprene units.…”
mentioning
confidence: 99%